The Impact of Bankruptcy Prediction, Company Growth, and Audit Quality on the Acceptance of Going Concern Audit Opinions - Muhamad Rivan Farizi; Lia Dahlia Iryani; Mulyaningsih, May (Tazkia Islamic University College, 2024)
This study aims to analyze the effect of bankruptcy prediction, company growth, and audit quality on the acceptance of going concern audit opinions. The research was conducted on cement sub-sector companies listed on the Indonesian Stock Exchange (IDX) from 2018 to 2022. The study utilizes a sample of annual financial statements audited by independent auditors. Data collection was performed by downloading audited annual financial reports. The analysis employed SPSS version 26, using logistic regression and hypothesis testing. The results indicate that, individually, bankruptcy prediction, company growth, and audit quality have no significant effect on the acceptance of going concern audit opinions. Additionally, simultaneous testing reveals that these factors do not have a significant collective impact on the issuance of going concern audit opinions in cement sub-sector companies listed on the IDX for the period 2018-2022.